Assessing neurodevelopmental effects of arsenolipids in pre‐differentiated human neurons. Issue 11 (29th August 2017) - Witt, Barbara; Ebert, Franziska; Meyer, Sören; Francesconi, Kevin A.; Schwerdtle, Tanja
Abstract : Scope: In the general population exposure to arsenic occurs mainly via diet. Highest arsenic concentrations are found in seafood, where arsenic is present predominantly in its organic forms including arsenolipids. Since recent studies have provided evidence that arsenolipids could reach the brain of an organism and exert toxicity in fully differentiated human neurons, this work aims to assess the neurodevelopmental toxicity of arsenolipids. Methods and results: Neurodevelopmental effects of three arsenic‐containing hydrocarbons (AsHC), two arsenic‐containing fatty acids (AsFA), arsenite and dimethylarsinic acid (DMA V ) were characterized in pre‐differentiated human neurons. AsHCs and arsenite caused substantial cytotoxicity in a similar, low concentration range, whereas AsFAs and DMA V were less toxic. AsHCs were highly accessible for cells and exerted pronounced neurodevelopmental effects, with neurite outgrowth and the mitochondrial membrane potential being sensitive endpoints; arsenite did not substantially decrease those two endpoints. In fully differentiated neurons, arsenite and AsHCs caused neurite toxicity. Conclusion: These results indicate for a neurodevelopmental potential of AsHCs. Taken into account the possibility that AsHCs might easily reach the developing brain when exposed during early life, neurotoxicity and neurodevelopmental toxicity cannot be excluded. Further studies are needed in order to progress the urgently needed risk assessment. Abstract : Neurodevelopmental effects as well as neurotoxic mechanisms of selected food‐relevant arsenolipids, namely arsenic‐containing hydrocarbons (AsHC) and arsenic‐containing fatty acids (AsFA), were studied in human pre‐differentiated and partly in fully differentiated neurons. The most sensitive endpoints turned out to be effects on mitochondrial membrane potential and neuronal network indicating that arsenolipids might exert substantial neurotoxicity and neurodevelopmental toxicity.